Liquid Biopsy in Squamous Cell Carcinoma of the Esophagus and of the Head and Neck - Iacob, Razvan; Mandea, Matei; Iacob, Speranta; Pietrosanu, Catalina; Paul, Doru; Hainarosie, Razvan; Gheorghe, Cristian (Frontiers in Medicine, 2022)
Squamous cell carcinomas of the esophagus (ESCC) and of the head and neck (HNSCC) are two neoplasms that share common risk factors and have the same embryological origin, but a very different prognostic, the 5-year survival of HNSCC being almost double (40-50%) compared to the 5-year survival of ESCC (20%). Current guidelines emphasize the importance of screening for esophageal squamous cell carcinoma in patients diagnosed with head and neck cancers. Liquid biopsy is a novel tool for diagnosis, prognostic stratification, and personalized therapy. Liquid biopsy biomarkers for these two malignancies could help both their early detection, facilitate residual disease identification, and provide prognosis information. The present systematic review of the literature was aimed at describing the liquid biopsy biomarkers present in these two pathologies, with an emphasis on potential clinical applications.